1995
DOI: 10.1128/jb.177.10.2834-2839.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an extracellular levansucrase from Pseudomonas syringae pv. phaseolicola

Abstract: Levansucrase (EC 2.4.1.10), an exoenzyme of Pseudomonas syringae pv. phaseolicola, was purified to homogeneity from the cell supernatant by chromatography on TMAE-Fraktogel and butyl-Fraktogel. The enzyme has molecular masses of 45 kDa under denaturing conditions and 68 kDa during gel filtration of the native form. In isoelectric focusing, active bands appeared at pH 3.55 and 3.6. Maximum sucrose cleaving activities were measured at pH 5.8 to 6.6 and 60؇C. The enzyme was highly tolerant to denaturing agents, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 48 publications
8
87
0
4
Order By: Relevance
“…This behaviour supports the idea that levans ful®l a crucial role during the early phase of infection by creating a separating layer between bacteria and plant cell wall polymers, in a way preventing recognition of the pathogen (Hettwer et al, 1995). Further straightforward evidence for the importance of levans during the plant±pathogen interaction comes from the fact that Erwinia amylovora strains de®cient in levansucrase had reduced virulence (Bereswill et al, 1997;Tharaud et al, 1994).…”
Section: Putative Functions Of Plant 6-fehssupporting
confidence: 57%
“…This behaviour supports the idea that levans ful®l a crucial role during the early phase of infection by creating a separating layer between bacteria and plant cell wall polymers, in a way preventing recognition of the pathogen (Hettwer et al, 1995). Further straightforward evidence for the importance of levans during the plant±pathogen interaction comes from the fact that Erwinia amylovora strains de®cient in levansucrase had reduced virulence (Bereswill et al, 1997;Tharaud et al, 1994).…”
Section: Putative Functions Of Plant 6-fehssupporting
confidence: 57%
“…However, the utilisable substrate range for Z. mobilis is restricted to glucose, fructose, and sucrose [1], and only sucrose should be recognised as an appropriate substrate for levan synthesis. It has been shown that multiform bacterial levansucrases can [1] or cannot [5] perform the polymerisation of fructose moiety from catabolised raffinose. There exists a lack of data concerning the kinetics and the products of such a reaction for Z. mobilis, excepting a few observations on the limited formation of levan on raffinose as compared to sucrose medium by the non-growing Z. mobilis ATCC 10988 [6] as well as on such an above-mentioned ability of a Z. mobilis levansucrase from a recombinant Escherichia coli [7] to perform this polymerisation.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Ohtsuka et al [19] and Hettwer et al [20] have shown that the activity and stability of the levansucrases from the Gram-negative bacteria Rahnella aquatilis and Pseudomonas syringae are not affected by the presence of calcium or EDTA.…”
Section: Sequence Alignments Of Members Of Family Gh68mentioning
confidence: 99%